Preparation for Childbirth Through Massage Effluerage Training, Hypnobirthing Yoga Exercises in Silian 1 Village, Silian District, Southeast Minahasa Regency - Sjenny Olga Tuju; Atik Purandari; Sandra G.J.Tombokan; Nanik Wahyuni; Fredrika Losu (Jurnal Nusantara Berbakti, 2023)
Pain in labor is a physiological process.contractions are used to divert women from pain during contractions, Yoga is a movement that is relatively safe and is performed on pregnant women, very useful for dealing with shortness of breath, back pain. Hypnobirthingdeep relaxation, through slow and deep breathing patterns so that the body automatically releases endorphins which are natural morphines in the body which are useful for reducing and even eliminating pain during contractionscan also increase the formation of endorphins DestinationIncrease the knowledge of midwives about effluerage massage and Hypnobirthing in pregnant women. The process of giving birth becomes very pleasant, smooth and fast with trainingeffluerage massageand hypnobirthing on imom is pregnant so that mothers enjoy a safe, gentle, smooth and comfortable delivery process through pregnant women classes in Silian Satu village, K1 and K4 in pregnant women will be achieved. After being evaluated from 10 pregnant women, there were 7 pregnant women who felt comfortable after doing effluerage massage followed by Hypnobirthing.